2011
DOI: 10.1111/j.1742-4658.2010.07990.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence of α‐aminoacylated lipoproteins of Staphylococcus aureus

Abstract: Bacterial lipoproteins are known to be diacylated or triacylated and activate mammalian immune cells via Toll‐like receptor 2/6 or 2/1 heterodimer. Because the genomes of low G+C content Gram‐positive bacteria, such as Staphylococcus aureus, do not contain Escherichia coli‐type apolipoprotein N‐acyltransferase, an enzyme converting diacylated lipoproteins into triacylated forms, it has been widely believed that native lipoproteins of S. aureus are diacylated. However, we recently demonstrated that one lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 33 publications
(65 reference statements)
5
59
0
Order By: Relevance
“…Fragments of tryptic lipopeptides observed in MALDI MS/MS spectra are mainly C-terminal-containing sequence ions (y-type), because the positive charge tends to localize at C-terminal lysine or arginine residues of the peptides. We confirmed that both diacyl and triacyl synthetic peptides [Pam2 (dipalmitoyl)-CSK 4 and Pam3-CSK 4 ] could be analyzed with respect to organic solvent extraction and ionization (3). The efficiencies of ionization of the synthetic diacyl and triacyl synthetic peptides are slightly different: the triacyl peptide was slightly more easily ionized than its diacyl counterpart in our MALDI-TOF MS analysis.…”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…Fragments of tryptic lipopeptides observed in MALDI MS/MS spectra are mainly C-terminal-containing sequence ions (y-type), because the positive charge tends to localize at C-terminal lysine or arginine residues of the peptides. We confirmed that both diacyl and triacyl synthetic peptides [Pam2 (dipalmitoyl)-CSK 4 and Pam3-CSK 4 ] could be analyzed with respect to organic solvent extraction and ionization (3). The efficiencies of ionization of the synthetic diacyl and triacyl synthetic peptides are slightly different: the triacyl peptide was slightly more easily ionized than its diacyl counterpart in our MALDI-TOF MS analysis.…”
Section: Methodssupporting
confidence: 63%
“…Proteins separated by SDS-PAGE were subjected to ingel digestion with trypsin, and the resulting digests (10 to 20 l) were acidified with 1 l of 70% formic acid and then mixed with the same volume of a chloroform/methanol mixture (2/1 [vol/vol]) to extract lipidmodified peptides. Finally, matrix-assisted laser desorption ionizationtime of flight (MALDI-TOF) mass spectrometry (MS) was performed on the lipopeptides in the lower organic phase as previously described (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our work was under review, an important study by Asanuma et al (27) appeared where the authors report that SitC and four other major lipoproteins from Staphylococcus aureus are triacylated despite the apparent absence of the lnt (N-acyltransferase) gene in this organism. It therefore appears that triacylation of lipoproteins is a global phenomenon in the bacterial world.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the protein band was performed as described (45). The protein band was excised from the gel, destained with 50% (vol/vol) methanol, and dried by vacuum centrifugation.…”
Section: Generation Of Complemented Strainsmentioning
confidence: 99%